KAJIAN TENTANG PERUBAHAN HARGA DALAM TRANSAKSI DENGAN SISTEM PEMBAYARAN CASH ON DELIVERY (COD) PADA ONLINESHOP SHOPEE MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Putri Damayanti; Zulfikar Jayakusuma; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The development of the internet provides many conveniences for humans tocontinue to make it easier to carry out their daily activities, including buying andselling. Many people create effective and efficient systems such as e-commerce. E-commerce is experiencing very rapid development so that companies createMarketplaces, one of which is Shopee. Shopee has a variety of payment systems,one of which is the Cash on Delivery (COD) system, Payment is made when thegoods reach the by buyer's. However, in this payment system there are somedrawbacks, such as price changes that occur when paying, two case about pricechanges experienced by some consumers that the author got from the Twitterplatform and one of the author's friends did not escape the incident. Things like thisare certainly very detrimental to consumers, because they require consumers to paymore than what is stated when they want to make a transaction. Based on the case,the authors are interested in studying, researching and relating this phenomenonbased on Law Number 8 of 1999 concerning Consumer Protection in writing thisthesis.The purpose of this research is to find out the COD system works on theShopee marketplace and protects consumers as a result of price changes intransactions with the COD payment system according to Law Number 8 of 1999concerning Consumer Protection. This research was conducted using a normativejuridical research approach. The method of normative juridical research approachis library law research which is carried out by examining library materials orsecondary data. In this study, the scope of research be carried out by drawing legalprinciples, which are carried out on written and unwritten positive laws.From the results of this study, that consumers should properly know therules and be careful when doing the transaction, consumers must set awarenessabout anything that harm. An institution is needed for consumer protection, whichsupervises consumer rights in e-commerce. Business actors must uphold highintegrity in carrying out their business. Electronic service providers should createa special service and complaint procedure for consumers who feel their rights arenot being fulfilled.Keywords: COD, Consumer, Shopee